A quantitative and qualitative assessment of sugar beet genotype resistance to root-knot nematode, Meloidogyne incognita - Gohar, Ibrahim M. A.; Alyamani, Amal; Shafi, Manal E.; Mohamed, Elshaimaa A. E.; Ghareeb, Rehab Y.; Desoky, Elsayed M.; Hasan, Mohamed E.; Zaitoun, Amera F.; Abdelsalam, Nader R.; El-Tarabily, Khaled A.; Elnahal, Ahmed S. M. (Frontiers in Plant Science, 2023)
Sugar beet productivity is highly constrained by the root-knot nematode (RKN) Meloidogyne incognita. Eight sugar beet genotypes were screened under greenhouse conditions for their susceptibility to M. incognita according to an adapted quantitative scheme for assignment Canto-Saenz’s host suitability (resistance) designations (AQSCS). Besides, the degree of susceptibility or tolerance of the examined genotypes was recorded by the modified host-parasite index (MHPI) scale based on yield performance. In addition, single nucleotide polymorphism (SNP) was also determined. Sugar beet genotypes have been classified into four categories for their susceptibility or tolerance according to the AQSCS scale. The first category, the moderately resistant (MR) group implies only one variety named SVH 2015, which did not support nematode reproduction (RF≤1), and had less root damage (GI≈2). Second, the tolerant group (T) involving Lilly and Halawa KWS supported fairly high nematode reproduction (RF>1) with relatively plant damage (GI≤2). Whereas the susceptible (S) category involved four varieties, FARIDA, Lammia KWS, Polat, and Capella, which supported nematode reproduction factor (RF>1) with high plant damage (GI>2). The fourth category refers to the highly susceptible (HYS) varieties such as Natura KWS that showed (RF≤1) and very high plant damage (GI>2). However, the MHPI scale showed that Lammia KWS variety was shifted from the (S) category to the (T) category. Results revealed significant differences among genotypes regarding disease severity, yield production, and quality traits. The SVH 2015 variety exhibited the lowest disease index values concerning population density with 800/250 cm3 soils, RF=2, root damage/gall index (GI=1.8), gall size (GS=2.3), gall area (GA=3.7), damage index (DI=3.4), susceptibility rate (SR=2.4), and MHP index (MHPI=2.5). However, Lammia KWS showed the highest disease index values regarding population density with 8890/250 cm3 soils, RF= 22.2, GI= 4.8, and SR= 14.1. Meanwhile, Natura KWS the highest GS, GA and MHPI with 7.1, 8 and 20.9, respectively. The lowest DI was achieved by Capella (DI= 6) followed by Lammia KWS (DI= 5.9). For yield production, and quality traits, SVH 2015 exhibited the lowest reductions of sugar yields/beet's root with 11.1%. While Natura KWS had the highest reduction with 79.3%, as well as it showed the highest reduction in quality traits; including sucrose, T.S.S, and purity with 65, 27.3, and 51.9%, respectively. The amino acid alignment and prediction of the DNA sequences revealed the presence of five SNPs among all sugar beet verities.